Writing an Effective Anticorruption Law - Messick, Richard E. (World Bank, Washington, DC, 2012)
The note looks at effective anticorruption legal instruments, ensuring that laws are in place to deter corruption. However, law enforcement measures are not the first, or necessarily the preferred method of defense. An informed citizenry, a government imbued with a service ethic, and other measures can be more effective in combating corruption. But tailoring the law to enforcement capacity, generally encompass a variety of statutes that prohibit bribery, nepotism, conflicts of interest, and favoritism in the award of contracts, or the provision of government benefits. And, writing such laws contain "bright-line rules" that are contrasted with those containing standards that are open to interpretation by enforcement agencies. As an example of these "bright-line rules" the note provides the recent example from Argentina, where nepotism, and favoritism in government hiring are perceived as serious problems. Considerations to the inclusion of bright-line rules include, the preclusion of receiving gifts or payments by government employees; of interest in a corporation or entity affected by that employee's decision; of hiring relatives; and, that employees must publicly disclose assets hold.